Analisis Prinsip 5C terhadap Pembiayaan Mudharabah di BMT Barokah Cabang Tegalrejo - Sofyana, Sonia; Fitriyani, Yeny; Aini, Qurotul (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2024)
Financing is the provision of funds by institutions to parties needing funds with a certain period in return, accompanied by the payment of several rewards or profit sharing. BMT is one of the Islamic financial institutions providing Islamic financing products. This study aims to analyze the application of the 5C principle in Islamic finance at BMT Barokah Tegalrejo. The research method used was the qualitative method with a descriptive approach. The research object is the BMT Barokah Tegalrejo branch. The source of information was obtained from interviews with Mr. Marfusaha, director of the BMT Barokah Tegalrejo branch. The results of this study indicate that the 5C principle is needed in Sharia financing to overcome problematic financing or bad credit. Suggestions for further research, research methods, and objects analyzed to be further expanded and detailed.